Suitability of Land in The Coastal Suburb of Tanah Bumbu Regency - Nazarullah Amin; Andy Mahreda; Nafa Celia H.D; Miftahul Akbar; Chika P. Rahali (Green Visioneers, 2018)
Tanah Bumbu Regency is one of the coastal areas that is one of the attractions of local or foreign tourists, but in line with the development of community activities, many settlements around the coastline and continue to increase every year. The coastal area is generally very attractive for fishermen to establish their housing because it is close to the place where they work as a fisherman in the sea. However, the existing settlements are often not concerned with the environment or applying regulations on development and management in coastal areas that have been set in government regulations such as Presidential Regulation No. 5 of 2016 concerning Beach Boundary Limits To discuss this, the research used is the method of reviewing papers or journals, regional government regulations and ministerial regulations, and will be compared and taken several things related to the field. Coastal Areas in Tanah Bumbu Regency are still not suitable. This is because there are no rules regarding the application of coastal boundaries in the coastal suburbs of Tanah Bumbu Regency.